Zilenial Teenagers' Perception Of Local Cultural Values 4s In Tamansari Bogor Subdistrict - Muslim, Muslim; Saleh, Amiruddin; Satria, Arif; Hapsari, Dwi Retno (UNIVERSITAS PAKUAN, 2023)
This study aims to analyze the perception of generation Z adolescents towards the local cultural values of 4S (Silih Asah, Silih Asih, Silih Asuh, and Silih Wangi) in Tamansari District, Bogor. The 4S local cultural value is a concept that represents the principles of local wisdom in terms of honing each other's knowledge and skills, loving and respecting each other, educating and guiding each other, and disseminating fragrance or kindness. This study used a qualitative approach with data collection methods through in-depth interviews and participatory observations. The study participants consisted of generation Z teenagers living in Tamansari District, Bogor. The collected data were analyzed using thematic analysis techniques to identify patterns of perceptions and views of adolescents towards local 4S cultural values. The results showed that the perception of generation Z adolescents towards the value of local 4S culture tends to vary. Some adolescents consider these values as important cultural heritage to maintain and practice in daily life, while others may lack understanding or interest in them. Factors such as modernization, globalization, and the influence of social media also influence adolescents' perceptions of local 4S cultural values. This research provides a deeper understanding of the perception of generation Z adolescents towards the value of local 4S culture in Tamansari District, Bogor. These findings can be used as a basis for efforts to preserve and develop local culture, particularly in the context of adolescents and the younger generation. In addition, this research also contributes to our understanding of the role of local cultural values in dealing with social changes occurring in today's society.